PENINGKATAN HASIL BELAJAR LARI 40 M DENGAN METODE DEMONTRASI DISDN 30 SANYANG LIPINUS SAKIMAN, MIMI HAETAMI, FITRIANA PUSPA HIDASARI PROGRAM STUDI PENDIDIKAN JASMANI EMAIL: SAKMAN@GMAIL.COM - Sakiman, Lipinus; Haetami, Mimi; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:The purpose of this study is to improve the learning outcomes of 40 m with the method of demonstration in students of class V In SDN 30 Sanyang. The purpose of this study to determine the increase of running 40 m by the method of demonstration in grade V students in SDN 30 Sanyang. The method used in this research is research type of classroom action research. The subject of this research is the teacher collaborate with the Class V Students at SDN 30 Sanyang Regency. Based on the results of research on the first cycle of students who have just graduated or completed as many as 12 students or 40% of students and who have not completed as many as 18 students or 60%. In order to get the value of a decent learning results it is necessary to make improvements, then proceed to cycle II by using students who can be categorized as pass or complete with 30 students or 100% and not complete 0 or no rule.Keywords: Run 40m, Demonstration